Using the Learn Arabic Application as a Learning Medium in Learning Arabic Vocabulary - agustin, sonia; Syafaati, Ummi; Syakban, Ismail (Jurnal Kajian dan Pengembangan Umat, 2025)
The use of the Learn Arabic application serves as an effective digital tool to enhance learners’ interest and motivation in studying Arabic vocabulary. This application not only supports vocabulary acquisition but also facilitates better comprehension and retention through interactive learning experiences. In the current era of advanced information technology, Learn Arabic offers an attractive alternative to conventional learning methods due to its accessibility, user-friendly interface, and engaging features. This study employed a qualitative descriptive approach aimed at exploring how the Learn Arabic application is utilized in learning Arabic vocabulary. The research involved active users of the application who regularly use it as a medium for developing their Arabic vocabulary. Data were collected through observation and interviews to understand user experiences and learning outcomes. The findings reveal that the Learn Arabic application significantly contributes to improving vocabulary mastery among learners. It offers a variety of interactive features, including vocabulary categorized by themes, pronunciation and writing exercises, as well as quizzes that strengthen memory retention. These features create an enjoyable and effective learning environment that encourages consistent practice and self-paced learning. Overall, the study concludes that the Learn Arabic application is a highly effective and practical resource for enhancing Arabic vocabulary learning in the digital eraKeywords: Application, Learn Arabic, Vocabulary, Arabic